The Effectiveness of Ethnoscience Learning Based on Local Wisdom Values in Elementary Schools - Hamna; Muh. Khaerul Ummah BK (Madako Elementary School, 2024)
The ethnoscience learning strategy is designed to develop students' ethnographic insight into scientific knowledge by combining modern science with traditional knowledge possessed by local communities or specific ethnic groups. As such, its implementation in elementary schools is highly relevant for developing students' appreciation of local wisdom values. The assessment of its effectiveness served as the primary basis for conducting this study, which was analyzed using a case study-based mixed-methods approach involving teachers and students from grades IV, V, and VI as a representation of the population at SDN 1 Nalu. The findings show that ethnoscience learning, based on strengthening local wisdom values, is highly effective in several ways: (1) increasing students' understanding of ethnoscience concepts; (2) improving students' critical thinking skills related to the development of local wisdom and scientific insights; (3) fostering the development of scientific attitudes; and (4) promoting the development of students' character in relation to local wisdom. The implications of these findings suggest that ethnoscience learning is an approach that stimulates the development of students' scientific concepts in connection with cultural heritage and the practice of local wisdom values in Tolitoli Regency, thereby increasing students' awareness of regional cultural heritage.